Miniplates coated by plasma electrolytic oxidation improve bone healing of simulated femoral fractures on low bone mineral density rats - Momesso, Gustavo Antonio Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The treatment of polytrauma patients represents a great challenge in the maxillofacial and orthopedic surgery fields. Therefore, this study tested the hypothesis that the use of a bioactive coating (by plasma electrolytic oxidation, PEO) on titanium microplates could improve the fracture healing of low bone mineral density (BMD) rats. Thirty female rats underwent bilateral ovariectomy surgery (OVX), and 35 rats underwent fake surgery (SHAM). Three months later, animals were subjected to femoral fracture simulation and were fixed with either non-coated (CONV) or coated (PEO) titanium miniplates. Eight weeks postoperatively, microplate/bone complexes were analyzed through computed microtomography, histometric, confocal microscopy, molecular, and biomechanical analysis. Bioactive elements (Ca and P) were incorporated on the PEO microplate and the surface was modified in a volcano-like structure. In the microCT analysis the OVX/PEO group had greater values for Tb.Th (bone trabecular thickness), Tb.Sp (separation of bone trabeculae) and Tb.N (number of trabeculae) parameters compared to the OVX/CONV group. According to histometric analysis, the OVX/PEO group showed significantly higher new bone formation than the OVX/CONV group (P < 0.05). For the fluorochrome area, the OVX groups (PEO and CONV) showed greater values for calcein precipitation (old bone) than alizarin red (new bone). Molecular results showed greater values for proteins related to the final phase of bone formation (P < 0.05) in the OVX/PEO group. The OVX/PEO group showed higher bone/miniplate system resilience compared to the others (P < 0.05). It was concluded that PEO coating optimizes bone healing on simulated femoral fractures in low bone mineral density rats. This sheds new light in the treatment of osteoporotic patients with bone fractures.

O tratamento de pacientes politraumatizados representa um grande desafio nas áreas de cirurgia maxilofacial e ortopédica. Portanto, este estudo testou a hipótese de que o uso de um revestimento bioativo (por oxidação eletrolítica de plasma, PEO) em microplacas de titânio poderia melhorar a cicatrização de fraturas de ratos com baixa densidade mineral óssea (DMO). Trinta ratas foram submetidas à cirurgia de ovariectomia bilateral (OVX) e 35 ratas foram submetidas à cirurgia falsa (SHAM). Três meses depois, os animais foram submetidos à simulação de fratura do fêmur, os quais foram fixados com miniplacas de titânio não revestidas (CONV) ou revestidas (PEO). Oito semanas de pós-operatório, os complexos miniplaca/osso foram analisados por meio de microtomografia computadorizada, histometria, microscopia confocal, análise molecular e biomecânica. Elementos bioativos (Ca e P) foram incorporados na miniplaca revestida por PEO e a superfície foi modificada em uma estrutura semelhante a um vulcão. Na análise microCT, o grupo OVX / PEO apresentou maiores valores para os parâmetros Tb.Th (espessura trabecular óssea), Tb.Sp (separação das trabéculas ósseas) e Tb.N (número de trabéculas) em comparação com o grupo OVX / CONV. De acordo com a análise histométrica, o grupo OVX / PEO apresentou formação de osso novo significativamente maior do que o grupo OVX / CONV (P <0,05). Para a área de fluorocromo, os grupos OVX (PEO e CONV) apresentaram maiores valores de precipitação de calceína (osso velho) do que vermelho de alizarina (osso novo). Os resultados moleculares mostraram maiores valores para proteínas relacionadas à fase final de formação óssea (P <0,05) no grupo OVX / PEO. O grupo OVX / PEO apresentou maior resiliência do sistema de osso / miniplaca em comparação com os demais (P <0,05). Concluiu-se que o revestimento PEO otimiza a consolidação óssea em fraturas femorais simuladas em ratos com baixa densidade mineral óssea. Isso lança uma nova luz no tratamento de pacientes osteoporóticos com fraturas ósseas.
Miniplacas texturizadas pela oxidação por plasma eletrolítico melhoram o reparo ósseo em simulações de fraturas femorais de ratas com baixa densidade mineral óssea
Keywords: Osteoporosis; Ovariectomy; Bone fractures; Fracture fixation internal; Osteoporose; Ovariectomia; Fraturas ósseas; Fixação interna de fraturas